Evaluation of the primary medical treatments based on the advanced trauma life support principles in trauma patients. (January 2022) - Asadi, Payman; Kasmaei, Vahid Monsef; Zia Ziabari, Seyyed Mahdi; Rimaz, Siamak; Modirian, Ehsan; Sarbazi-Golezari, Ali
Objective: In Iran, road traffic accidents were responsible for 14716 deaths in 2015. This study aimed to compare the initial resuscitation of traumatically injured patients to the internationally recognized ATLS standards. Materials and methods: As a cross-sectional study, 506 traumatically injured patients who were referred to the tertiary referral major trauma center in Poursina Hospital during the study period, were evaluated. All therapeutic interventions were compared to the ATLS standards. Data on mortality by demographic was compared to those in whom the ATLS standards were met and in those whom it was not met Results: Mean age of the patients was 37.37 ± 19.72 and motorcycle was the most common cause of accidents (40.9%). ATLS guideline interventions were completely performed in 18.2% of the patients in their primary hospital, and in rest of 414 cases (81.8%), ATLS algorithms were not fully carried out. The mortality rate was significantly higher in the second group: 10.86% vs 32.36%, respectively. Conclusion: Application of ATLS principles in multiple trauma patients can reduce the mortality rate.